KEBIJAKAN KEIMMIGRASIAN, KREATIVITAS DAN KOMPETENSI KERJA SERTA PENGARUHNYA TERHADAP KINERJA ASN KANTOR IMMIGRASI KELAS 1 TPI TANJUNG PERAK - Rohandi Manumpak Tua Hamonangan; Tri Ratnawati (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to determine and analyze Immigration Policy, Creativity, Work Competence and Their Influence on the Performance of ASN Immigration Office Class 1 TPI Tanjung Perak. The population is ASN Immigration Office Class 1 TPI Tanjung Perak totaling 100 people and the sampling technique using the survey method or saturated sample by taking all members of the population as respondents. Using questionnaires to collect primary data. The analytical tool used is multiple linear regression with SPSS Version 21 program. The results show that Immigration Policy has a positive and significant effect on the performance of ASN Performance of ASN Immigration Office Class 1 TPI Tanjung Perak, Creativity has a positive and significant effect on ASN Performance Class 1 TPI Immigration Office Tanjung Perak, Work Competence has a positive and significant impact on the performance of ASN Immigration Office Class 1 TPI Tanjung Perak